Effectiveness of Individual Counseling Services Using Solution Focused Brief Therapy Approach to Reduce Smoking Behavior of Manggarai Students - Yohanes Bagung; Leny Latifah; Imam Ariffudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Smoking behavior is the act of burning any tobacco product that is intended to be burned, smoked, and inhaled, including clove cigarettes, white tobacco, cigars or other forms produced from the Nicotina plant, tabacum or other synthetic products whose smoke contains nicotine and tar. Researchers use individual counseling services with the Solution Focused Solution Therapy (SFBT) approach. The purpose of this study was to reduce smoking behavior in FIP Manggarai students, Universitas PGRI Kanjuruhan Malang. The method used in this study is an experimental method with a single subject design. The population used by researchers were Manggarai students, FIP, Universitas PGRI Kanjuruhan Malang, by taking a sample of 1 person and sampling was carried out by researchers using a purposive sampling technique. The results of the subject intervention were able to reduce the frequency, intensity and duration of smoking, Subject AD began to develop a higher awareness of the negative impacts of smoking, both for the health of the subject himself and the surrounding environment. In addition, the subject also showed increased self-confidence in facing the temptation to smoke, especially when in a social situation that was previously the main trigger.